“Fika in the Anthropocene”: leveraging food systems transformations through food cultures - Anne Charlotte Bunge; Michael Clark; Line J. Gordon (Sustainability Science, 2025)
The role of food cultures in food systems transformations is gaining prominence in scholarly discourse. However, several food cultures rely on products with substantial environmental and socio-economic impacts and risks, raising questions about their potential role in transformation processes toward more sustainable food systems. One such example constitutes the Swedish Fika , the daily practice of having coffee and pastries in company as an important social care institution. Based on ingredients like coffee, cocoa, and palm oil, it relies on products associated with high environmental and socio-economic impacts and risks. This paper draws on resilience theory and uses pathways as a conceptual approach to explore how Fika as an illustrative food cultures can be adapted to societal targets and anthropogenic challenges in order to preserve its deeper social value in the long term. We first outline the interlinked environmental and socio-economic impacts and threats associated with Fika ingredients. We then develop two distinct exemplary pathways, “less but better” and “innovated” Fika , to illustrate potential strategies that could mitigate adverse impacts while enhancing its resilience to anthropogenic challenges. Finally, we discuss the potential of these pathways to leverage wider dietary transitions by permeating throughout the food system. We propose that viewing individual food products within their cultural context ( the food cultural lens ) provides the opportunity for a paradigm shift, using food cultures as strategic entry points and levers for wider food system transformation. Further multi- and transdisciplinary research is required to evaluate the effectiveness of these pathways as well as the broader potential of food cultures to leverage food system change.

Corporate concentration and power matter for agency in food systems - Jennifer Clapp; Rachael Vriezen; Amar Laila; Costanza Conti; Line Gordon; Christina Hicks; Nitya Rao (Food Policy, 2025)

Top-down vs bottom-up processes: A systematic review clarifying roles and patterns of interactions in food system transformation - Costanza Conti; Andy Hall; Enayat A. Moallemi; Amar Laila; Christophe Bene; Jessica Fanzo; Matthew Ford Gibson; Line Gordon; Christina Hicks; Kristiaan Kok; Nitya Rao; Ramanan Laxminarayan; et al. (Global Food Security, 2025)

Nurturing gastronomic landscapes for biosphere stewardship - Amanda Jonsson; L. Jamila Haider; Laura Pereira; Alexander Fremier; Carl Folke; Maria Tengö; Line J. Gordon (Global Food Security, 2024)

Malin Falkenmark: Water pioneer who coined the notion of water crowding and coloured the water cycle - Johan Rockström; Lan Wang-Erlandsson; Carl Folke; Dieter Gerten; Line J. Gordon; Patrick W. Keys (Ambio, 2024)

Organic agriculture in a low-emission world: exploring combined measures to deliver a sustainable food system in Sweden - Shyam Basnet; Amanda Wood; Elin Röös; Torbjörn Jansson; Ingo Fetzer; Line Gordon (Sustainability Science, 2023)
In the EU, including Sweden, organic farming is seen as a promising pathway for sustainable production, protecting human health and animal welfare, and conserving the environment. Despite positive developments in recent decades, expanding organic farming to the Swedish national target of 30% of farmland under organic production remains challenging. In this study, we developed two scenarios to evaluate the role of organic farming in the broader context of Swedish food systems: (i) baseline trend scenario ( Base ), and (ii) sustainable food system scenario ( Sust ). Base describes a future where organic farming is implemented alongside the current consumption, production and waste patterns, while Sust describes a future where organic farming is implemented alongside a range of sustainable food system initiatives. These scenarios are coupled with several variants of organic area: (i) current 20% organic area, (ii) the national target of 30% organic area by 2030, and (iii) 50% organic area by 2050 for Sust . We applied the ‘FABLE (Food, Agriculture, Biodiversity, Land-use and Energy) Calculator’ to assess the evolution of the Swedish food system from 2000 to 2050 and evaluate land use, emissions and self-sufficiency impacts under these scenarios. Our findings show that expanding organic farming in the Base scenarios increases the use of cropland and agricultural emissions by 2050 compared to the 2010 reference year. However, cropland use and emissions are reduced in the Sust scenario, due to dietary changes, reduction of food waste and improved agricultural productivity. This implies that there is room for organic farming and the benefits it provides, e.g. the use of fewer inputs and improved animal welfare in a sustainable food system. However, changing towards organic agriculture is only of advantage when combined with transformative strategies to promote environmental sustainability across multiple sections, such as changed consumption, better production and food waste practices.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Our future in the Anthropocene biosphere - Carl Folke; Stephen Polasky; Johan Rockström; Victor Galaz; Frances Westley; Michèle Lamont; Marten Scheffer; Henrik Österblom; Stephen R. Carpenter; F. Stuart Chapin; Karen C. Seto; Elke U. Weber; et al. (Ambio, 2021)
The COVID-19 pandemic has exposed an interconnected and tightly coupled globalized world in rapid change. This article sets the scientific stage for understanding and responding to such change for global sustainability and resilient societies. We provide a systemic overview of the current situation where people and nature are dynamically intertwined and embedded in the biosphere, placing shocks and extreme events as part of this dynamic; humanity has become the major force in shaping the future of the Earth system as a whole; and the scale and pace of the human dimension have caused climate change, rapid loss of biodiversity, growing inequalities, and loss of resilience to deal with uncertainty and surprise. Taken together, human actions are challenging the biosphere foundation for a prosperous development of civilizations. The Anthropocene reality—of rising system-wide turbulence—calls for transformative change towards sustainable futures. Emerging technologies, social innovations, broader shifts in cultural repertoires, as well as a diverse portfolio of active stewardship of human actions in support of a resilient biosphere are highlighted as essential parts of such transformations.

Correction to: The great Green Wall for the Sahara and the Sahel initiative as an opportunity to enhance resilience in Sahelian landscapes and livelihoods - Deborah Goffner; Hanna Sinare; Line J. Gordon (Regional Environmental Change, 2019)

The Great Green Wall for the Sahara and the Sahel Initiative as an opportunity to enhance resilience in Sahelian landscapes and livelihoods - Deborah Goffner; Hanna Sinare; Line J. Gordon (Regional Environmental Change, 2019)

Sustainable intensification of agriculture for human prosperity and global sustainability - Johan Rockström; John Williams; Gretchen Daily; Andrew Noble; Nathanial Matthews; Line Gordon; Hanna Wetterstrand; Fabrice DeClerck; Mihir Shah; Pasquale Steduto; Charlotte de Fraiture; Nuhu Hatibu; et al. (Ambio, 2017)

The Anthropocene: From Global Change to Planetary Stewardship - Will Steffen; Åsa Persson; Lisa Deutsch; Jan Zalasiewicz; Mark Williams; Katherine Richardson; Carole Crumley; Paul Crutzen; Carl Folke; Line Gordon; Mario Molina; Veerabhadran Ramanathan; et al. (Ambio, 2011)

Understanding relationships among multiple ecosystem services - Elena M. Bennett; Garry D. Peterson; Line J. Gordon (Ecology Letters, 2009)
Ecology Letters (2009) 12: 1394–1404 Abstract Ecosystem management that attempts to maximize the production of one ecosystem service often results in substantial declines in the provision of other ecosystem services. For this reason, recent studies have called for increased attention to development of a theoretical understanding behind the relationships among ecosystem services. Here, we review the literature on ecosystem services and propose a typology of relationships between ecosystem services based on the role of drivers and the interactions between services. We use this typology to develop three propositions to help drive ecological science towards a better understanding of the relationships among multiple ecosystem services. Research which aims to understand the relationships among multiple ecosystem services and the mechanisms behind these relationships will improve our ability to sustainably manage landscapes to provide multiple ecosystem services.

Soil feedback drives the mid-Holocene North African monsoon northward in fully coupled CCSM2 simulations with a dynamic vegetation model - Samuel Levis; Gordon B. Bonan; Cline Bonfils (Climate Dynamics, 2004)